2008
DOI: 10.1140/epjd/e2008-00137-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl sulphide under strong laser field: Time-dependent density functional theory

Abstract: To be published in The European Physical Journal D Abstract. The first 52 fs of a time evolution of the electron density in OCS after an interaction with an intense sub 10 fs laser pulse are studied using the time-dependent density functional theory. The nuclear motion in this linear trimer is simulated by the classical molecular dynamics method. Laser fields of intensity 10 13 W/cm 2 and 10 15 W/cm 2 are used. Details of the laser induced changes of the structure, as well as the ionization rate are sensitive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…This suggests that in our experiment, with intensity ∼1 × 10 14 W/cm 2 and wavelength 2 µm, corresponding to a laser period of 6.6 fs, the molecular structure remains essentially unchanged during the time interval between ionization to recollision. In this context we note that recent ab-initio calculations 40 for laser pulses centered at 790 nm and an intensity of 1 × 10 15 W/cm 2 have shown that the atomic distances and bending angle ∠(O-C-S) are changing on a timescale longer than 10 fs, i. e., longer than the optical period in our experiment.…”
Section: Resultssupporting
confidence: 47%
“…This suggests that in our experiment, with intensity ∼1 × 10 14 W/cm 2 and wavelength 2 µm, corresponding to a laser period of 6.6 fs, the molecular structure remains essentially unchanged during the time interval between ionization to recollision. In this context we note that recent ab-initio calculations 40 for laser pulses centered at 790 nm and an intensity of 1 × 10 15 W/cm 2 have shown that the atomic distances and bending angle ∠(O-C-S) are changing on a timescale longer than 10 fs, i. e., longer than the optical period in our experiment.…”
Section: Resultssupporting
confidence: 47%
“…Table 2 summarizes the potential energies and oscillator strengths for the first four excited electronic states of neutral OCS. Our results agree with previous ab initio calculations 40 . Moreover, in order to minimize the computational effort, simulations assume instantaneous delta pulse excitation to the excited state at the beginning of the simulation.…”
Section: Methodssupporting
confidence: 93%
“…These authors assigned the recoil velocities from the (O 3+ , C 3+ , S 4+ ) channels to a bent structure (Φ OCS = 140°) just prior to Coulomb explosion. Recent ab initio calculations at 0.8 μm also revealed that structural deformation in OCS occurs on a timescale longer than 13 fs 40 , with wave packet simulations reporting that a linear-to-bent transition occurs on a 50-fs timescale, reaching an OCS bond angle of ~135° 37 .…”
Section: Resultsmentioning
confidence: 96%
“…It is well known that the electron localization function (ELF) has become an important tool for a description of chemical bonds in molecules and solids. [26,27] Recently, Burnus et al [28] illustrated the usefulness of the time-dependent ELF in analyzing the creation and breaking of bonds. The two-dimensional representations of the ionic structure and the ELF contour plots for linear C 4 in the 𝑥𝑦 plane, the 𝑦𝑧 plane and the 𝑥𝑧 plane at 𝑡 = 0 fs and 𝑡 = 25 fs when the electron emission already reaches the saturation are presented in Fig.…”
Section: -2mentioning
confidence: 99%